Use of Genetically Modified Bacteria to Modulate Adaptive Immunity - Bueno, Susan M.; Gonzalez, Pablo A.; Kalergis, Alexis M. (Current Gene Therapy, 2009)
Infectious diseases caused by virulent bacteria are a significant cause of morbidity and mortality worldwide, especially in developing countries. However, attenuated strains derived from pathogenic bacteria, such as Salmonella, are highly immunogenic and can be used as vaccines to promote immunity against parental pathogenic bacteria strains. Further, they can be genetically manipulated to either express foreign antigens or deliver exogenous DNA, in order to induce immunity against other pathogens or antigens. Contrarily, specific structural modifications in attenuated Salmonella have allowed the generation of strains that can be well tolerated by the immune system and reduce inflammatory responses. It is thought that those strains could be considered as vectors to promote specific immune tolerance for certain auto-antigens or allergens and reduce unwanted or self-reactive immune responses. In addition, some structural features of Salmonella can contribute to defining the nature and type of polarization of the adaptive immune response induced after immunization, which can be considered as a tool to modulate antigen-specific immunity. In this article we discuss recent advances in the understanding of immune system modulation by molecular components of bacteria and their exploitation for the rational induction of pathogen immunity or antigen-specific tolerance.